In utero exposure to cannabidiol disrupts select early-life behaviors in a sex-specific manner - Daniela Iezzi; Alba Caceres-Rodriguez; Pascale Chavis; Olivier J. J. Manzoni (Translational Psychiatry, 2022)
Abstract Cannabidiol (CBD), one of the main components of cannabis, is generally considered safe. CBD crosses the placenta and its use during pregnancy is steadily increasing, the impact of gestational CBD’s effects on prenatal life and neurodevelopment are poorly understood. Here, we combined behavioral approaches and deep learning analysis to assess the sex-dependent neonatal behavior of CBD exposed progeny. Gestating C57BL6/J dams were exposed daily with vehicle or CBD (3 mg/Kg, s.c.), from gestational day 5 to 18. Body weight, pup ultrasound vocalizations (USVs, PND 10) and homing behavior (PND 13) were quantified in the progeny. Thus, male (but not female) pups from CBD-treated dams gained more weight than sham. There were sex-dependent differences in the coarse characteristics of ultrasonic vocalizations. Prenatally-CBD exposed male pups emitted shorter calls, whereas CBD females made more high frequency calls when compared with their control counterparts. There were significant qualitative changes in the syllabic USV repertoire reflected in call typologies and communication patterns. Finally, the homing behavior test showed that CBD-exposed females presented a greater vulnerability to gestational CBD than males. Only CBD-exposed female pups showed reduced motor and discriminatory abilities. Together the results suggest a sexual divergence in the consequences of in utero CBD exposure on neonates at early developmental ages, which may be predictive of adult psychopathology. Given the extent of cannabis and CBD use worldwide, these findings challenge the idea that CBD is a universally safe compound and reveal the need for additional studies on the effect of perinatal CBD exposure.